La Regla de Oro, entre el Amor y la Justicia. Signaturas políticas y teológicas en la ética de Paul Ricoeur - Martín Grassi (Franciscanum, 2017)
Our task in this paper is to take forward a creative and critique reading of Paul Ricoeur’s Ethics, in order to show the semantical displacements towards the idea of Justice that moves from Ethics to Moral, from Formal to Material, from Singular to Political, and from Ethical to Theological meanings. We will focus on the operational sense of Justice, on what we call its economic sense, and on its reference to Alterity. This ambivalence of Justice can be thought from the dialectics between Love and Justice, and mainly be detected in the case of the Golden Rule. Is in this Rule where we should find confirmations of the ethical, political and theological signatures that surrounds the very notion of Justice.